Global Agenda for Social Justice : Volume One - Shefner, Jon, 1958-; Perrucci, Robert; Muschert, Glenn W.; Klocke, Brian V.; Christian, Michelle; Budd, Kristen M. (Book collections on Project MUSE., 2018)
"The Global Agenda for Social Justice provides accessible insights into some of the world's most pressing social problems and proposes international public policy responses to those problems. Written by a highly respected team of authors brought together by the Society for the Study of Social Problems (SSSP), chapters examine topics such as criminal justice, media concerns, environmental problems, economic problems, and issues concerning sexualities and gender. They offer recommendations for action by governing officials, policy makers, and the public around key issues of social justice. It will be of interest to scholars, practitioners, advocates, and students interested in public sociology, the study of social problems and the pursuit of social justice."--